TRANSFORMASI DIGITAL UNTUK MENINGKATKAN AKURASI DAN EFISIENSI PENCATATAN UMKM - Khilda Aulia Larasati; Dendy Kurniawan; Sumaryanto Sumaryanto (Jurnal Padamu Negeri, 2025)
Digital transformation is a strategic solution to address manual recording problems still prevalent among Micro, Small, and Medium Enterprises (MSMEs). This community service activity was conducted at Toko Anugerah, an MSME located in Mangkang Wetan, Semarang City, which previously relied on handwritten transaction records. Through a participatory approach, the service team provided training and assistance in implementing a digital recording system using Google Spreadsheet. The results showed significant improvements in recording efficiency, data accuracy, and ease of information access. In addition, the store owner and staff also demonstrated increased digital literacy. This success confirms that simple and appropriate technology, supported by intensive mentoring, can effectively encourage MSMEs to undertake digital transformation.